Bioavailability Investigation of Two Different Oral Formulations of Methylprednisolone - Geister, Ursula; Guserle, Richard; Bungers, Eva; Schaarschmidt, Dieter; Doser, Karlheinz (Arzneimittelforschung, 2000)
Two different oral methylprednisolone (CAS 83-43-2) formulations (Methylprednisolon-ratiopharm 8 mg tablets as test preparation (T) and tablets of a reference preparation (R)) were investigated in 16 healthy volunteers in order to prove bioequivalence between these preparations. A single 8 mg oral dose was given according to a randomised two-way crossover design in the fasted state. Blood samples for determination of methylprednisolone plasma concentrations were collected at pre-defined time points up to 16 h following drug administration. A washout period of 3 days separated both treatment periods.Methylprednisolone plasma concentrations were determined by means of a validated HPLC method. Values of 342.53 ng • h/ml (test preparation) and 336.61 ng • h/ml (reference preparation) for the parameter AUC0-> demonstrate an nearly identical extent of drug absorption. Maximum concentrations (Cmax) of 66.58 ng/ml and 70.51 ng/ml were achieved for test and reference preparation. Time to reach maximum plasma concentration (tmax) was 2.2 h for both preparations. Cmax and AUC0->-values were tested parametrically by the two one-sided t-test procedure. Bioequivalence was concluded if the 90% confidence intervals of the T/R-ratios were in the range of 80-125% for AUC0-> and 70-143% for Cmax.Based on the results obtained in this study, bioequivalence between Methylprednisolone ratiopharm and the reference preparation was demonstrated.
Keywords: CAS 83-43-2; High-pressure liquid chromatography; Methylprednisolone; Methylprednisolone ratiopharm, bioavailability, bioquivalence